Effects of diversification and portfolio performance of the ceramic sector of Bangladesh - Jalil, Rubaiyat Al (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.